Efektivitas Neurofeedback Training Terhadap Emosi dan Interaksi Sosial Pada Anak Autis di Pusat Kajian Psikologi Magister Psikologi Pascasarjana Universitas Medan Area - Mawaddah Rahmah; Sri Milfyetty; Risydah Fadilah (Universitas Medan Area, 2021)
This This study aims to test the effectiveness of Neurofeedback Training to overcome emotional problems and social interactions of children with autism. This study used a Quasi Experiment One Group Pretest - Posttest Design method. The sampling technique used Purposive Sampling and the research sample was 1 person. The research instrument is a measurement of brain wave activity called Electroencephalography. The data analysis of this research resulted in two types of data, quantitative and qualitative data. Quantitative data is the result of scores and graphs of measuring brain waves of autistic children through Neurofeedback and qualitative data is the result of assessment using DSM V, observation results and interview reports. The hypothesis proposed is that Neurofeedback Training is effective in overcoming emotional problems and social interactions in children with autism. The conclusions in this study are: 1. Neurefeedback training is effective in overcoming emotional problems of children with autism, this is shown by increasing the Alpha value of 18 Hz. 2. Neurefeedback Training is effective in overcoming the social interaction problem of children with autism, this is shown by increasing the Sensorymotor Rhytm value of 5 Hz. 3. Neurefeedback Training is effective in overcoming emotional problems and social interactions in children with autism, this is indicated by an increase in the Alpha value of 18 Hz, the Sensorymotor Rhytm value of 5 Hz and the Beta value of 13 Hz. Based on the conclusion, the proposed hypothesis is accepted. For future researchers who want to research Neurofeedback, they can use subjects in children with special needs with different disorders.